Quality of care at childbirth during the COVID-19 pandemic in Belgium: a cross-sectional study based on WHO standards - Marzia Lazzerini; Emanuelle Pessa Valente; Enrico Lopriore; Mariana Pereira; Helen Elden; Ilaria Mariani; Anna Galle; Christoph Zenzmaier; Nicos Middleton; Antonella Nespoli; Dace Rezeberga; Mehreen Zaigham; et al. (BMJ Open)
Objectives To examine quality of maternal and newborn care (QMNC) around childbirth in facilities in Belgium during the COVID-19 pandemic and trends over time.Design A cross-sectional observational study.Setting Data of the Improving MAternal Newborn carE in the EURO region study in Belgium.Participants Women giving birth in a Belgian facility from 1 March 2020 to 1 May 2023 responded a validated online questionnaire based on 40 WHO standards-based quality measures organised in four domains: provision of care, experience of care, availability of resources and organisational changes related to COVID‐19.Primary and secondary outcome measures Quantile regression analysis was performed to assess predictors of QMNC; trends over time were tested with the Mann‐Kendall test.Results 897 women were included in the analysis, 67% (n=601) with spontaneous vaginal birth, 13.3% (n=119) with instrumental vaginal birth (IVB) and 19.7% (n=177) with caesarean section. We found overall high QMNC scores (median index scores>75) but also specific gaps in all domains of QMNC. On provision of care, 21.0% (n=166) of women who experienced labour reported inadequate pain relief, 64.7% (n=74) of women with an instrumental birth reported fundal pressure and 72.3% (n=86) reported that forceps or vacuum cup was used without their consent. On experience of care, 31.1% (n=279) reported unclear communication, 32.9% (n=295) reported that they were not involved in choices,11.5% (n=104) stated not being treated with dignity and 8.1% (n=73) experienced abuse. Related to resources, almost half of the women reported an inadequate number of healthcare professionals (46.2%, n=414). Multivariable analyses showed significantly lower QMNC scores for women with an IVB (−20.4 in the 50th percentile with p<0.001 and 95% CI (−25.2 to −15.5)). Over time, there was a significant increase in QMNC Score for ‘experience of care’ and ‘key organisational changes due to COVID-19’ (trend test p< 0.05).Conclusions and relevance Our study showed several gaps in QMNC in Belgium, underlying causes of these gaps should be explored to design appropriate interventions and policies.Trial registration number NCT04847336.